Daya Hambat Ekstrak Rumput Laut Spesies Eucheuma Cottonii Terhadap Pertumbuhan Bakteri Mixed Periodontopatogen - Iqbal Fahmiliyan Asmoro; Yoifah Rizka; Paulus Budi Teguh (Denta Journal Kedokteran Gigi, 2015)
Background: Bacterial mixed periodontopatogen dominated by gram negative. Eucheuma cottonii seaweed as one of the plant species have the antibacterial effect againts gram positive and gram negative bacteria.thus potentially developed as antibacterial agent in periodontal disease. Purpose: This study aimed to determine the inhibition effect of Eucheuma cottonii seaweed extract to the growth of mixed periodontopathogen bacteria concentration of 0,25%, 0,5%, 1% and 2%. Materials and Methods: Eucheuma cottonii seaweed extracted with 95% etanol by soxhlet method. Mixed periodontopathogen bacteria inoculated in BHI medium. Antibacterial effects of extracts of Eucheuma cottonii seaweed againts bacterial mixed periodontopathogen was tested by the diffusion method with the concentrations of 0,25%, 0,5%, 1%, 2%, aquadest and tetracycline, where each group consisted of 5 experiment unit. The effect of the inhibition observed by measuring the diameter of clear area on the disk using digital calipers stated in millimeters. Result: There were inhibition effect at each concentrations of treatment. The diameter zone were concentration of 0.25% (6.184), the concentration of 0.5% (6.356), the concentration of 1% (6.62), the concentration of 2% (7.148) and a positive control with tetracycline (39.336) Conclusion: Eucheuma cottonii seaweed extract has inhibition effect to the growth ofbacteria mixed periodontopatogen.